2004
DOI: 10.1104/pp.103.036590
|View full text |Cite
|
Sign up to set email alerts
|

Two New Alleles of the abscisic aldehyde oxidase 3 Gene Reveal Its Role in Abscisic Acid Biosynthesis in Seeds

Abstract: The abscisic aldehyde oxidase 3 (AAO3) gene product of Arabidopsis catalyzes the final step in abscisic acid (ABA) biosynthesis. An aao3-1 mutant in a Landsberg erecta genetic background exhibited a wilty phenotype in rosette leaves, whereas seed dormancy was not affected (Seo et al., 2000a). Therefore, it was speculated that a different aldehyde oxidase would be the major contributor to ABA biosynthesis in seeds (Seo et al., 2000a). Through a screening based on germination under high-salt concentration, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 30 publications
2
50
0
2
Order By: Relevance
“…The double mutants were also more sensitive than single parental mutants to inhibition of germination and early growth mediated by osmotic stress. Imposing osmotic stress at the seedling stage leads to increased ABA biosynthesis and consequently to early growth arrest (Lopez-Molina et al, 2001;Gonzalez-Guzman et al, 2004). Thus, whereas in adult plants ABA plays a crucial role to coordinate the various aspects of the low water potential response to allow plant survival, in seeds and seedlings ABA action is mainly focused to prevent germination and to arrest seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…The double mutants were also more sensitive than single parental mutants to inhibition of germination and early growth mediated by osmotic stress. Imposing osmotic stress at the seedling stage leads to increased ABA biosynthesis and consequently to early growth arrest (Lopez-Molina et al, 2001;Gonzalez-Guzman et al, 2004). Thus, whereas in adult plants ABA plays a crucial role to coordinate the various aspects of the low water potential response to allow plant survival, in seeds and seedlings ABA action is mainly focused to prevent germination and to arrest seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…The hormone ABA has been involved in postharvest quality and stress tolerance of fruit (Serrano et al, 2004;Alférez et al, 2005;Cantín et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological characterization of the Arabidopsis aao3 mutant showed an ABA-deficient phenotype, osmotolerance in germination and wilty leaves (Seo et al, 2004;González-Guzman et al, 2004;Barrero et al, 2006). In addition, Seo et al (2004) demonstrated that these mutants (AAO1-AAO4) displayed reduced or not affected dormancy because a partial redundancy among genes.…”
Section: Physiological Effects Of the Aba Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Este fenotipo leve en las semillas se ha atribuido a la redundancia de genes postulándose que otros genes de AAOs podrían estar implicados en la biosíntesis de ABA [222]. Aunque la identificación de alelos nulos aao3 que exhiben fenotipos deficientes en ABA importantes en semillas indican que probablemente AAO3 es único gen de las AAOs que participa en la síntesis de ABA [66,221].…”
Section: Biosíntesis Del áCido Abscísicounclassified